Evaluation of Perception of Use of a Gamified Platform from the Student Perspective: An Approach for Studying Unified Modeling Language - Feichas, Felipe A; Seabra, Rodrigo D (Informatics in education, 2023)
This research discusses the use of a gamified web platform for studying software modeling with Unified Modeling Language (UML). Although UML is constantly being improved and studied, many works show that there is difficulty in teaching and learning the subject, due to the complexity of its concepts and the students’ cognitive difficulties with abstraction. There are challenges for instructors to find different pedagogical strategies to teach modeling. The platform proposed allowed students to complement their UML knowledge in an environment with game elements. From the results, it can be concluded that the platform obtained great acceptance and satisfaction of use. Most of the students participating in the research were satisfied with the usability of the platform, reporting a feeling of contribution of the tool to studying the content, in addition to pointing out the satisfaction of using gamification as a pedagogical strategy.